PENGEMBANGAN DAN PENERAPAN KONTEN H5P PADA E-LEARNING BERBASIS LMS MENGGUNAKAN MOODLE - Meisye Anastacya Pinoa (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
E-learning is a system that utilizes information technology in the learning process. The application of information technology in e-learning learning by using Moodle can be modified to simplify the learning process by using the H5P feature (interactive content). Interactive content (H5P) is content and learning materials in the LMS e-learning system which aims to make it easier for everyone to create, compare and reuse interactive HTML5 content. The purpose of this research is to design interactive content that attracts the attention of users in the use of e-learning and to create attractive interactive content using the Design Sprint model method. This method consists of 5 stages, namely understand, diverge, decide, prototype, and validation. The Design Sprint Model method has a systematic process for producing effective interactive content to be presented using website-based information technology on the e-learning portal. In this study, researchers will develop interactive content which initially only contains learning material such as ppt. The results of th e development and application of H5P content on LMS-based e-learning using moodle, among others, focuses on how much the user understands the use of interactive content developed. The test results show that the feedback or results on the development and application of H5P content on LMS-based e-learning using moodle about material created online are aimed at an increase in the results of the interactive video content task, which is more dominant than the results of the interactive content task book.